THE IMPORTANCE OF MARKETING IN SUPPORTING BUSINESS DEVELOPMENT - Anwar, Raihan Aid; Ramadhan, Rama (Journal for Management Student (JFMS), 2024)
In this era of globalization, business competition is getting tougher, so companies must pay attention to one important aspect in facing this very tight competition, namely marketing. Marketing is a process of planning and developing business activities which includes pricing, promotion and distribution of a number of ideas, goods or services directed at an exchange process that satisfies individual and organizational goals. By using a marketing strategy in running a business, companies are expected to be able to face competition, retain customers, as well as gain new customers for business development for a company.